The impacts of Crocin on serum cytokines concentrations in participants with metabolic syndrome: a double-blind randomized clinical trial study - Razie Rezaiee; Hamideh Ghazizadeh; Susan Darroudi; Roshanak Ghaffarian Zirak; Mohadese Rohban; Marziyeh Eidi; Irandokht Nikbakht Jam; Ali Asghar Mahmoudi; Farzin Hadizadeh; Malihe Aghasizadeh; Abbas Mohtashamian; Majid Ghayour-Mobarhan (Scientific Reports)
Abstract The aim of this study was to investigate the effect of Crocin on the inflammatory cytokines profile in patients with Metabolic syndrome (Mets). Twenty-eight patients with Mets (15 cases and 13 controls) were randomly selected by the International Diabetes Federation (IDF) definite criteria in a double-blind randomized clinical trial. Participants were divided into two treatment groups, a group received 15 mg of Crocin (two tablets per day), and the other one received a placebo for eight weeks. Inflammatory and growth factors were measured using a sandwich chemiluminescence assay, before and after treatment. Our results indicated that inflammatory factors including IL-2, IL-10, VEGF and INF γ, were significantly reduced (P < 0.05) in patients with Mets after Crocin treatment. Moreover, no significant difference was detected among the other biochemical factors (lipid profile and FBG) between two groups. The results showed the exclusive impact of Crocin on the reduction of serum inflammatory cytokines. Crocin has the potential to be further investigated as a useful therapeutic factor in inflammatory diseases. Clinical trial registration number: IRCT2013080514279N1, Registration date: 01/02/2015.